2019
DOI: 10.1158/1078-0432.ccr-18-4222
|View full text |Cite
|
Sign up to set email alerts
|

Loss of ARID1A in Tumor Cells Renders Selective Vulnerability to Combined Ionizing Radiation and PARP Inhibitor Therapy

Abstract: Purpose: Somatic inactivating mutations in ARID1A, a component of the SWI/SNF chromatin remodeling complex, are detected in various types of human malignancies. Loss of ARID1A compromises DNA damage repair. The induced DNA damage burden may increase reliance on PARP-dependent DNA repair of cancer cells to maintain genome integrity and render susceptibility to PARP inhibitor therapy. Experimental Design: Isogenic ARID1A À/À and wild-type cell lines were used for assessing DNA damage response, DNA compactness, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
77
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 39 publications
5
77
1
2
Order By: Relevance
“…Eventually, through loss of p53, or upregulation of oncogenic networks like Myc or stem cell transcription factors, a subset of Arid1a-depleted precursor cells progress to frank adenocarcinomas. Our data reassesses the utility of therapeutic vulnerabilities previously described in other ARID1A mutant cancer models (e.g., DNA repair defects or microsatellite instability), in the setting of PDAC 24,25,55 , while describing novel opportunities for targeting this class of cancers in the clinic.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Eventually, through loss of p53, or upregulation of oncogenic networks like Myc or stem cell transcription factors, a subset of Arid1a-depleted precursor cells progress to frank adenocarcinomas. Our data reassesses the utility of therapeutic vulnerabilities previously described in other ARID1A mutant cancer models (e.g., DNA repair defects or microsatellite instability), in the setting of PDAC 24,25,55 , while describing novel opportunities for targeting this class of cancers in the clinic.…”
Section: Discussionsupporting
confidence: 78%
“…Specifically, Arid1a localizes to sites of DSBs through its interaction with DNA repair checkpoints, with loss of Arid1a leading to compromised homologous recombination repair (HR) and non-homologous end joining (NHEJ), the two major arms of DSB repair. Further, these studies have also shown increased sensitivity of cell lines with ARID1A mutations to DSB inducing agents like cisplatin, radiation and to PARP inhibitors 24,25 . Surprisingly, our "KAC" cells were both relatively resistant to Cisplatin and PARP inhibitors (compared to the "KC" and "KPC" lines), and by the Comet assay, their DNA repair proficiency was comparable to these Arid1a wild type PDAC lines.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations